Achieving maximum recovery of latent heat in photothermally driven multi-layer stacked membrane distillation. (February 2021) - Ghim, Deoukchen; Wu, Xuanhao; Suazo, Mathew; Jun, Young-Shin
Abstract: Photothermal membrane distillation (PMD) has received increased attention for water desalination because it uses abundant sunlight as its main energy source. It can also be implemented in a modular configuration and work well for decentralized communities. Here we present a multi-layer stacked membrane module with airgaps that can reduce conductive heat loss and recover latent heat. The membrane is synthesized by a simple and scalable spray-coating method that prepared by graphene nanosheets deposition onto a hydrophobic polytetrafluoroethylene (PTFE) membrane with polymerized dopamine (PDA) and trichloro(1H, 1H, 2H, 2H-perfluorooctyl) silane (FTCS). Graphene nanosheets are employed as a photothermal material because of its broad light absorption in the solar spectrum and efficient photothermal conversion. To maximize the water flux, the airgap thickness was optimized, and multiple heat recovery layers were stacked. Using the optimized airgap and four stacked layers, we achieved a high water flux of 1.17 kg/m 2 /h under 0.75 kW/m 2, equivalent to 105% solar conversion efficiency, which is the highest efficiency reported among all PMD studies (20–70%). To predict the water flux, we further constructed a theoretical model to estimate the membrane surface temperatures that are photothermally heated, which will be helpful in understanding and optimizing future PMD systems. The high efficiency of the multi-layer stacked PMD module in this study bespeaks its great promise as a sustainable and off-grid desalination technique. Graphical Abstract: ga1 With an efficient graphene nanosheet-based photothermal membrane, we demonstrate that the performance of the photothermal membrane distillation was largely improved by effectively recovering latent heat generated during condensation of vapor. Using the optimized airgap and four stacked layers, we achieved a high water flux of 1.17 kg/m 2 /h under 0.75 kW/m 2, equivalent to 105% solar conversion efficiency. Highlights: Graphene-based photothermal membranes were fabricated with a simple spray coating. In our novel multi-layer stacked module, latent heat was efficiently recovered. With an optimal setting, we achieved the high solar-to-water efficiency (~ 105%). Synthesized membranes were mechanically and chemically robust for long-term use.